Comparative Analysis of Scientific and Applied Approaches in the Sphere of Psychological Services - Babajanyan, Irina (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
This article aims to conduct a comparative analysis of modern approaches to the application of methods of psychological assessment and practice (counseling, therapy, training, etc.), which are obtained from the results of the content analysis of scientific literature and Internet resources of psychological organizations. The relevance of the presented study is associated with modern challenges of a socio-economic and psychological nature and the modernization of the conditions for research, counseling and therapy. Generalization of observations and scientific information indicates that the transformations of recent years have influenced the form and format of interaction between the parties of the psychological service: psychologist-client. The conclusions of the theoretical analysis indicate that the authors of articles and studies do not always indicate the criteria adopted by international or national associations of psychologists. It is also difficult to assess the reliability of studies conducted in different countries, since the ethical principles of the research psychologist are not specified. Content analysis made it possible to determine the features of the presentation, promotion and positioning of psychological services in three countries (Armenia, USA, Russia).